Performance analysis of ultrathin junctionless double gate vertical MOSFETs - K. E. Kaharudin; Z. A. F. M. Napiah; F. Salehuddin; A. S. M. Zain; Ameer F. Roslan (Bulletin of Electrical Engineering and Informatics, 2019)
The main challenge in MOSFET minituarization is to form an ultra-shallow source/drain (S/D) junction with high doping concentration gradient, which requires an intricate S/D and channel engineering. Junctionless MOSFET configuration is an alternative solution for this issue as the junction and doping gradients is totally eliminated. A process simulation has been developed to investigate the impact of junctionless configuration on the double-gate vertical MOSFET. The result proves that the performance of junctionless double-gate vertical MOSFETs (JLDGVM) are superior to the conventional junctioned double-gate vertical MOSFETs (JDGVM). The results reveal that the drain current (ID) of the n-JLVDGM and p-JLVDGM could be tremendously enhanced by 57% and 60% respectively as the junctionless configuration was applied to the double-gate vertical MOSFET. In addition, junctionless devices also exhibit larger ION/IOFF ratio and smaller subthreshold slope compared to the junction devices, implying that the junctionless devices have better power consumption and faster switching capability.